Indo-U.S. FTA: Prospects for Audiovisual Services - Arpita Mukherjee; Paramita Deb Gupta; Prerna Ahuja (Indian Council for Research on International Economic Relations (ICRIER), 2007)
Many WTO (World Trade Organization) member countries, including India, are defensive about opening up of the audiovisual sector in the Doha Round due to reasons of cultural sensitivity. On the other hand, the United States is pushing for liberalizing trade in this sector - both in the WTO and in its bilateral FTAs (Free Trade Agreements). With the slow progress of the Doha Round, India and the United States are exploring the possibilities of entering into FTAs with like-minded trading partners. In this context, the present paper discusses the prospects of liberalizing audiovisual services under a possible Indo-U.S. FTA. The study found that India and the United States have significant trade complementarities in this sector which can be further enhanced under an FTA. It identifies areas such as co-production of films, digital content creation and broadband infrastructure in which companies from India and the United States can enter into mutually beneficial collaborations. It argues that India should enter into a media cooperation agreement with the U.S. to facilitate the inflow of technical know, finance and best management practices. It discusses regulatory and other reforms which would not only improve the productivity and global competitiveness of the Indian audiovisual sector but also enable it to gain from the FTA.
Keywords: F13; F14; L82; 330; Indo-U.S. FTA; GATS; bilateral agreements; audiovisual; services; Freihandelszone; Internationale Wirtschaftsbeziehungen; GATS; Handelsliberalisierung; Mediensektor; Indien; USA